2013
DOI: 10.1371/journal.pone.0082348
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeography and Spatiotemporal Spread of South-Central Skunk Rabies Virus

Abstract: The south-central skunk rabies virus (SCSK) is the most broadly distributed terrestrial viral lineage in North America. Skunk rabies has not been efficiently targeted by oral vaccination campaigns and represents a natural system of pathogen invasion, yielding insights to rabies emergence. In the present study we reconstructed spatiotemporal spread of SCSK in the whole territory of its circulation using a combination of Bayesian methods. The analysis based on 241 glycoprotein gene sequences demonstrated that SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 47 publications
0
37
1
Order By: Relevance
“…In turn, the RAC-SK group contained a number of ‘subclades’ corresponding to Mexican skunks (MeSK-1), North American raccoons (RAC) and South-Central skunks (SCSK) as previously described (S3 Fig) [14, 16, 17, 39]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the RAC-SK group contained a number of ‘subclades’ corresponding to Mexican skunks (MeSK-1), North American raccoons (RAC) and South-Central skunks (SCSK) as previously described (S3 Fig) [14, 16, 17, 39]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that RABV isolates fall into two major phylogenetic groups; the bat- and the dog-related RABV groups [8, 13, 14]. The ‘bat-related’ RABV group is confined to New World viruses circulating mainly among bats, as well as in some terrestrial carnivores such as skunks and raccoons [1417]. In contrast, the ‘dog-related’ RABV group contains viruses circulating worldwide in dogs, as well as in wildlife carnivores in specific geographic areas such as foxes and raccoon dogs in Europe, foxes in the Middle East, raccoon dogs and ferret-badgers in Asia, skunks, foxes, coyotes and mongooses in the Americas, and mongooses in Africa [14, 16, 1822].…”
Section: Introductionmentioning
confidence: 99%
“…While the first analysis consists of testing the impact of environmental factors on dispersal velocity, we have also used a new approach that aims at testing the impact of such factors on the dispersal direction, that Note: For each statistic, we report both the median value and 95% HPD interval. In addition to the Iranian RABV data set introduced in the present study, we also report dispersal statistics estimated for several previously published RABV data sets: bat RABV data sets from Argentina (Torres et al, 2014), Brazil (Vieira, Pereira, Carnieli, Tavares, & Kotait, 2013) and Peru (Streicker et al, 2016), raccoon and skunk RABV data sets from North America Kuzmina et al, 2013) and a dog RABV data set from northern Africa (Talbi et al, 2010). "n" indicates the number of sequences in each data set.…”
Section: Impact Of Environmental Factors On Viral Lineage Dispersalmentioning
confidence: 99%
“…Phylogeographic approaches have previously been used to study the dynamics and spread of RABV at both large (Biek, Henderson, Waller, Rupprecht, & Real, ; Horton et al, ; Kuzmina et al, ; Talbi et al, ; Troupin et al, ) and small geographical scales (Bourhy et al, ; Zinsstag et al, ). Here, we use continuous phylogeographic analyses as well as related post hoc approaches to study the dispersal history of RABV spread in Iran and to investigate the environmental factors impacting its dispersal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no effective treatment after declaration of the disease, there is an effective management against RABV and related lyssaviruses when applied as soon as possible after exposure, it consists of local treatment of the wound, administration of rabies immunoglobulin (if indicated) and vaccinations against rabies that is able to prevent the onset of symptom and death [13]. Moreover, even with well-studied and documented epidemic expansions of wildlife RABV, there is little to know about the spread of rabies in endemic areas [14]. The replication potentials of various lyssaviruses looks different in a given host and the genome organization is highly conserved [15,16].…”
Section: Introductionmentioning
confidence: 99%